Membaca Pemahaman Hadis Muḥammad Al-Ghazālī dan Yūsuf Al-Qarḍāwī: Studi Kasus Pemikiran Suryadi - Muhammad Alfatih Suryadilaga (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2020)
The understanding of ḥadīth as a part of the problem that develops in society becomes the most important part of ḥadīth study. Its existence becomes an interesting study and produces a variety of certain thoughts studied in various scientific works. One of the thoughts on the understanding of the ḥadīth is examined by Suryadi in his dissertation that has been published under the title of contemporary methods of understanding the ḥadīth Prophet’s perspective Muḥammad al-Ghazālī and Yūsuf al-Qarḍāwī. This article discusses Suryadi’s reading about Muhammad al-Gazali’s and Yusuf Qardawi’s thoughts on Ḥadīth. Using a descriptive-analytic method this study scrutinizes how both discuss ḥadīth in modern context. Based on the collected and analized data, this study finds that both scholars introduce new method of understanding a ḥadīth considering the important of modern context. It also finds that both relate their discussion to the maqasid of Islam, that is raḥmatan li-al-’ālamīn.